2012
DOI: 10.1002/jcb.24144
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs miR‐96, miR‐124, and miR‐199a regulate gene expression in human bone marrow‐derived mesenchymal stem cells

Abstract: MicroRNAs are small non-coding RNAs that control gene expression at the post-transcriptional level by binding to 3'-untranslated regions (3'-UTR) of their target mRNAs. They present a promising tool to delineate the molecular mechanisms regulating differentiation of human mesenchymal stromal cells (hMSCs) and to improve the controlled differentiation of hMSCs in therapeutic applications. Here we show that three microRNAs, miR-96, miR-124, and miR-199a, were differentially expressed during osteogenic, adipogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 46 publications
2
88
0
1
Order By: Relevance
“…How-ever, several reports have shown that miR-124 is also expressed in non-neuron tissues/cells, such as pancreas (47), breast (11), bone marrow-derived mesenchymal stem cells (48), and lung (49), and has functions in these tissues. Pulmonary artery smooth muscle cells in the adult are highly specialized cells that regulate vessel tone through the expression of a unique repertoire of SMC-specific genes, such as ␣-SMA, SM22␣, smooth muscle myosin heavy chain (SM-MHC), and calponin (50).…”
Section: Discussionmentioning
confidence: 99%
“…How-ever, several reports have shown that miR-124 is also expressed in non-neuron tissues/cells, such as pancreas (47), breast (11), bone marrow-derived mesenchymal stem cells (48), and lung (49), and has functions in these tissues. Pulmonary artery smooth muscle cells in the adult are highly specialized cells that regulate vessel tone through the expression of a unique repertoire of SMC-specific genes, such as ␣-SMA, SM22␣, smooth muscle myosin heavy chain (SM-MHC), and calponin (50).…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs (miR-1247, miR-145, miR-140, and miR-199a) have been reported to exert an effect on chondrogenesis by eventually affecting Sox9 expression positively (Karlsen et al 2013) or negatively (Laine et al 2012, Martinez-Sanchez et al 2012, Martinez-Sanchez & Murphy 2013. Of all the miRNAs affecting chondroblast differentiation, miR-140 has received the most research attention to date (He et al 2009, Nakamura et al 2011, Gibson & Asahara 2013, Karlsen et al 2013, Papaioannou et al 2013).…”
Section: Mirnas and Chondroblast Differentiationmentioning
confidence: 99%
“…miR-96, miR-124, and miR-199a have been studied in human BMMSCs and have been found to be differentially expressed during osteogenic, adipogenic, or chondrogenic induction: whereas miR-124 is expressed exclusively in adipocytes, the expression of miR-199a is upregulated in osteoblasts and chondrocytes (Laine et al 2012).…”
Section: Mirnas and Chondroblast Differentiationmentioning
confidence: 99%
“…Studies on the genetic and epigenetic mechanisms that control the differentiation potential of hMSCs have focused on characterizing variation in both mRNA and miRNA expression levels [18][19][20][21]. MicroRNAs (miRNAs) control cell fate by negatively regulating protein accumulation through effects on the stability and/or translation of mRNAs for transcription factors and their phenotypic target genes.…”
Section: Introductionmentioning
confidence: 99%